Prevalence of Listeria monocytogenes in food samples from retail shops and street vendor stalls in Pretoria and the evaluation of bacterial probiotics as potential control measure - Thantsha, Mapitsi Silvester (University of Pretoria, 2020)
Dissertation (MSc)--University of Pretoria, 2020.